Dehumanization of people with dementia: perception of uniquely human nature characteristics - Pionk, Timothy D. (My University, 2018)
This study assessed how Human Nature (HN) and Uniquely Human (UH) characteristics affected moral status, attitudes toward, and willingness to interact with a female target with dementia. A short narrative described six events depicting Betty R. as being higher or lower on HN and UH characteristics. The results indicate that UH characteristics did not significantly affect participants’ attitudes toward or their desire to interact with the target person, while the absence of HN characteristics resulted in more negative attitudes toward and reduced desire to interact with the target person. Participants reported the highest levels of empathic concern for the target person when she showed lower levels of both HN and UH characteristics and the lowest levels of empathic concern when the target showed lower levels of HN and higher levels of UH characteristics. Higher levels of UH characteristics resulted in increased blame for immoral acts and increased perceived thought the target puts into her actions, while higher levels of HN characteristics showed the same relationship but to a lesser degree. Both sets of characteristics resulted in increased perceptions of pain felt but did not affect praise for moral actions or likelihood of intervening if treated immorally. Implications of these findings for dehumanization and humanization of persons with dementia are discussed.
"A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science Psychology-Cognitive and Affective."
Keywords: Dementia; Human nature characteristics; Uniquely human characteristics